Research progress on masticatory function assessment tools and influencing factors in patients after mandibular reconstruction - ZHANG Yue; GU Fen; WANG Yueping; YANG Wenyu; ZHAO Xiaomei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Mandibular reconstruction refers to the restoration of the continuity of the mandible through techniques such as autologous bone grafting, thereby restoring the patient's basic appearance, reconstructing the occlusal relationship, and restoring functions such as opening the mouth, chewing, and swallowing, in order to achieve a unity of oral and maxillofacial forms and functions. Due to the fact that mastication necessitates the coordinated efforts of the masticatory muscles, mandible, dental arch, and tongue, the recovery of masticatory function not only serves as a robust indicator for the success of surgery but also enhances the patients' quality of life, facilitating an early return to normal life. Currently, for the rehabilitation of oral function in patients after mandibular reconstruction surgery, standardized tools have been established in the fields of swallowing, occlusion, and speech assessment, and targeted training has been implemented, yielding significant therapeutic outcomes. However, research related to masticatory function faces two major challenges. First, existing assessment tools primarily focus on a single dimension, such as masticatory efficiency or subjective perception, and an integrated assessment system that encompasses multiple dimensions, including bite force distribution and oral sensory perception, has not yet been established. Second, although individual studies have explored factors affecting postoperative masticatory function, a systematic consensus has not been veached, leading to a lack of precision and individualization in clinical interventions, which significantly prolongs the patients' rehabilitation period. This paper reviews the scope and limitations of existing assessment tools for masticatory function in patients after mandibular reconstruction and systematically analyzes the key factors affecting postoperative masticatory function, aiming to promote a shift in clinical practice from "structural reconstruction" to a "function-perception collaborative rehabilitation" approach, and to provide a theoretical framework for constructing evidence-based, personalized masticatory rehabilitation programs.